Sistem pengelolaan kayu rakyat di pegunungan kapur selatan (Studi Kasus Hutan Rakyat di Desa Girisekar, Kecamatan Panggang, Kabupaten Gunung Kidul, DIY)=Smallholder Timber Production System At South Karst Mountain(Case - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACTSmallholders forest development at south karst mountain, firstly urged by the circumstance of the forest, which had experienced damage. That damage was caused by the wrong management which disobeying the social aspects. It results a degradation of forest that runs continuously so that the forest could not meet the necessities of society anymore. Therefore, the alternative of meeting the society's necessities, one way was to increase the smallholder forest development.This research was conducted in Girisekar Village, which the area was exist a smallholder forest had been producing and the local society had enjoyed the benefit. This research was aimed to find out, how did the society manage their own field to determine a tactic toward the Limit of natural resource to meet their life necessities.The objective of this research was to find out the dynamics of smallholder forest development, the smallholder timber anagement system and also to find out the condition of smalholder timber marketing management. The results of the research showed that the dynamics of smallholders forest development in Girisekar Village tended to be positive, provided by the annual increase of forest actual width and the more variously wood, especially for the commercial plants. According to the observation, the smallholder timber management system in Girisekar, detected that the dominant kind of wood volume (teak, Mahogany, Acacia) - 484.74 m3. The manufacture of wood as craftsmanship wood and firewood. the needs of craftsmanship wood per capita per year. The necessity of firewood per village per year = 17,879.6 m3 per year. The condition of marketing system in Girisekar still could not raise to the optimal sale level, because the highest profit was on the gatherer stage and the marketing of smallholders timber by the farmer done to meet the immediate necessity.